Preparation of the protein corona: How washing shapes the proteome and influences cellular uptake of nanocarriers. (15th September 2020) - Brückner, Maximilian; Simon, Johanna; Jiang, Shuai; Landfester, Katharina; Mailänder, Volker
Abstract: A protein coat, termed the protein corona, assembles around the nanocarriers´ surface once it gets in contact with a biological environment. We show that the media used for the washing of protein corona can be crucial. This is true for the downstream analysis as well as for the pre-coating used in in vitro or in vivo . This has been widely overlooked so far. In this paper we focus on eight different washing media and analyze how they influence the composition of the hard protein corona of several nanocarriers incubated with human blood plasma and serum. SDS-PAGE and LC-MS analysis showed major differences in protein corona profiles when using diverse washing media. While plasma and serum proteins already have different complexities, each washing media changes the composition of proteins detected by downstream methods with different key proteins bound to the nanocarriers´ surface. Furthermore, the protein structure of the most abundant blood proteins incubated in the different media was analyzed with nanoDSF. This also emphasized the importance of the washing media, which had a significant influence on the protein adsorption stability. Lastly, cell uptake experiments for HeLa and RAW 264.7 macrophages also indicated an influence of the washing media. In conclusion, picking a specific washing media is on the one hand an important factor for downstream detection of protein compositions and may on the other hand be used to deliberately tune the protein corona for pre-adsorbed proteins from complex protein compositions. This might further support a guided delivery of the nanocarrier to a desired location within a physiological environment. Statement of Significance: The successfully application of nanocarriers as drug delivery vehicles is currently hampered by a limited understanding of the nanocarriers´ behavior in a complex biological environment. Once the nanocarrier comes into contact with blood plasma or serum, biomolecules rapidly adsorb onto their surface, covering the nanocarriers and forming a protein corona, which then dictates their biological identity. Analyzing the composition of this dynamic network of bound molecules, has already been shown to be influenced by various factors. However, the impact of the washing media used for the protein corona preparation has so far been neglected. In the present study, we demonstrate a quantitative influence of the washing media on the composition of the hard corona of different nanocarrier systems, which additionally affects protein stability and cellular uptake behavior. Graphical abstract: Image, graphical abstract